2017
DOI: 10.1111/gcb.13712
|View full text |Cite
|
Sign up to set email alerts
|

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic

Abstract: Somatic growth is an integrated, individual-based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio-indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas, which are long-lived, highly migratory, primarily herbivorous mega-consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 63 publications
2
65
1
2
Order By: Relevance
“…Although similarities in terms of movements were observed between the five foraging grounds, it is also worth mentioning the strong inter-site and inter-individual variability. The high degree of plasticity in sea turtles' movements and home ranges has already been recorded in numerous studies [17,89,[92][93][94], but this is the first time such plasticity has been demonstrated by a metaanalysis of juvenile green turtles' movements tracked from five contrasted sites from the same Regional Management Unit [95]. Inter-individual variability could be attributed to both intrinsic (e.g.…”
Section: Resultsmentioning
confidence: 76%
“…Although similarities in terms of movements were observed between the five foraging grounds, it is also worth mentioning the strong inter-site and inter-individual variability. The high degree of plasticity in sea turtles' movements and home ranges has already been recorded in numerous studies [17,89,[92][93][94], but this is the first time such plasticity has been demonstrated by a metaanalysis of juvenile green turtles' movements tracked from five contrasted sites from the same Regional Management Unit [95]. Inter-individual variability could be attributed to both intrinsic (e.g.…”
Section: Resultsmentioning
confidence: 76%
“…De eilanden lijken ook in belangrijkheid snel toe te voor de functie als foerageergebied Bjorndal, 2017). Het gebied van Lac-baai blijkt zelfs een van de beste foerageergebieden te zijn voor de Soepschildpad, alwaar deze soort de hoogste groeisnelheden van de gehele Caribische regio vertoont (Bjorndal et al, 2017 Esteban et al, 2015).…”
Section: Relatief Belang Binnen Het Caribisch Gebied: Beperktunclassified
“…Het gebied van Lac-baai blijkt zelfs een van de beste foerageergebieden te zijn voor de Soepschildpad, alwaar deze soort de hoogste groeisnelheden van de gehele Caribische regio vertoont (Bjorndal et al, 2017 Esteban et al, 2015). Het leggen en uitkomen van nesten vindt hoofdzakelijk plaats van april-oktober.…”
Section: Relatief Belang Binnen Het Caribisch Gebied: Beperktunclassified
“…These genetic data suggest that juvenile green sea turtle occurrence in the Bay of Biscay likely results from a combination of Gulf Stream/North Atlantic Current transport and stochastic storm events, similar to loggerheads (Monzón-Argüello et al 2012). Correspondingly, green sea turtle age and growth data generated by the current analyses were compared with those from juvenile foraging populations along the US Atlantic and Gulf coasts and western South Atlantic (Zug & Glor 1998, Goshe et al 2010, Avens et al 2012, Bjorndal et al 2017, Lenz et al 2017, thought to originate from some of the same source populations (Bass & Witzell 2000, Bass et al 2006.…”
Section: Methodsmentioning
confidence: 99%